Effectiveness of TNF inhibitor switch in RA: results from the national Swedish register. Issue 5 (15th January 2014) - Chatzidionysiou, Katerina; Askling, Johan; Eriksson, Jonas; Kristensen, Lars Erik; van Vollenhoven, Ronald
Abstract : Background: Switching to a second tumour necrosis factor inhibitor (TNFi) after discontinuation of a first in rheumatoid arthritis (RA) is a common strategy. The reason for the switch from the first TNFi could potentially influence the response to therapy. Data on direct comparisons between TNFi after switching are limited. Methods: The national Swedish register was used. RA patients who switched to a second TNFi (infliximab, etanercept or adalimumab) after failure of a TNFi as first-ever biologic were identified. Effectiveness of treatment was compared across the three drugs according to the first TNFi used, the reason for discontinuing and the drug survival. Drug survival across TNFi used as second biologic was compared. Results: Half of all patients starting infliximab, adalimumab or etanercept during the period 2005–2012 discontinued treatment for various reasons. Of these patients, a third switched within 2 months to a second TNFi (infliximab, etanercept or adalimumab). Around 35% of all patients achieved low disease activity or remission at 6 months. Regarding the switching strategy, best results were observed among patients who switched from infliximab to etanercept because of (secondary) inefficacy. Etanercept as second TNFi was associated with longer drug survival compared with infliximab. Conclusions: Switching to a second TNFi after the failure of the first may lead to good clinical results. The inter-drug differences in drug survival on the second TNFi mirror those reported previously for the first TNFi, suggesting that these differences are not solely due to channelling bias.